Morphology and phosphate distribution in bottom ash particles from fixed-bed co-combustion of sewage sludge and two agricultural residues - Strandberg, Anna (Waste management (New York, N.Y.), 2024)
Copyright © 2024 The Author(s). Published by Elsevier Ltd.. All rights reserved.